Business Development Executive Divisi Start-Up Development di PT. Hashmicro Solusi Indonesia - Anggre Firda Yani; Muhammad Ghazi; Tita Deitiana; Satriyo Wibowo (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2022)
In the era of Globalization 4.0, competition of work field is the world of work is increasingly challenging, where fresh graduates are required to prepare themselves starting from soft skills and hard skills. Therefore, the government provides a place for students by providing opportunities to develop skills to work directly on real projects. Participating in the internship activities, the author gains insight and learns new things. This report contains the author's experience in conducting internships at PT HashMicro Solusi Indonesia as a Business Development Executive with the role of Trainer and Implementation. Author’s job and responsiility are, teaching clients how to use the recruitment system to find the best qualified candidate, reporting if clients have any problem, and checking client’s database for any error that may occur.